Analisis Peran Audit Internal Dalam Mendeteksi dan Mencegah Kesalahan Operasional Pembiayaan (Studi Kasus Pada Bank Sumut Syariah KCP Hamparan Perak) - Hutapea, Nandini Falensya; Liswanty, Ina; Masyitah, Emi (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the role of internal audit in addressing operational errors in the financing cycle at PT. Bank Sumut Syariah KCP Hamparan Perak. The research background is based on initial findings of administrative errors, such as incorrect input of contract dates, which indicate weaknesses in internal control. The study employs a qualitative approach through interviews, observations, and validation using source triangulation. The results show that the most frequent operational errors occur in administrative aspects, particularly data entry mistakes by Account Officers, which directly affect customer installment schedules and bank reporting. Internal audit plays a dual role as both a watchdog and a consultant as well as a catalyst for change. Through the application of risk-based auditing, recommendations, and follow-up actions, internal audit effectively contributes to preventing recurring errors and continuously strengthening the effectiveness of internal control.